Interactive physical and biotic factors control dissolved oxygen in salmon spawning streams in coastal Alaska - Jason B. Fellman; Eran Hood; Sonia Nagorski; John Hudson; Sanjay Pyare (Aquatic Sciences, 2019)

Contemporary genetic structure of brown bears ( Ursus arctos ) in a recently deglaciated landscape - Tania M. Lewis; Sanjay Pyare; Kris J. Hundertmark (Journal of Biogeography, 2015)
Aim We examined contemporary genetic structure of brown bears ( Ursus arctos ) in a recently deglaciated landscape to identify the number and geographical range of populations, the level of admixture, landscape features that limit or promote genetic connectivity, and probable population sources of bears in Glacier Bay following the end of the Little Ice Age ( LIA ). We sought to determine whether brown bears exhibit genetic structure corresponding with landscape features and whether source populations of recent colonizers could be determined using nuclear genetic markers. Location Southeast Alaska is composed of many islands, fjords and ice‐covered lands with a complex history of changing glaciation and sea level throughout the Pleistocene and into the Holocene. Glacier Bay was again covered by ice during the LIA until c . 260 years ago when rapid retreat began exposing land for colonization. Methods We used DNA microsatellites to examine the genetic diversity of 105 brown bears. We identified the number of genetically distinct populations and the degree of admixture using Bayesian allele frequency assignment tests, determined colonizing population sources based on fixation and differentiation indices, and tested correlations between the genetic relatedness and a suite of landscape models. Results The shoreline of Glacier Bay hosts brown bears from at least two distinct genetic populations which may represent contemporary colonizing sources. There is also indication of a third group specific to Glacier Bay that may represent a historical colonizing population. The three genetic populations overlap in northern Glacier Bay, with relatively low admixture between the populations, indicating current immigration. Main conclusions Glacier Bay fjord inhibits dispersal and funnels recolonizing bears from east and west refugia in a northward direction. At the northern end of Glacier Bay these populations are currently coming into secondary contact after hundreds and possibly thousands of years of separation, creating a population‐level biological contact zone.

Climate change implications in the northern coastal temperate rainforest of North America - Colin S. Shanley; Sanjay Pyare; Michael I. Goldstein; Paul B. Alaback; David M. Albert; Colin M. Beier; Todd J. Brinkman; Rick T. Edwards; Eran Hood; Andy MacKinnon; Megan V. McPhee; Trista M. Patterson; et al. (Climatic Change, 2015)

Temporal patterns in adult salmon migration timing across southeast Alaska - Ryan P. Kovach; Stephen C. Ellison; Sanjay Pyare; David A. Tallmon (Global Change Biology, 2015)
Pacific salmon migration timing can drive population productivity, ecosystem dynamics, and human harvest. Nevertheless, little is known about long‐term variation in salmon migration timing for multiple species across broad regions. We used long‐term data for five Pacific salmon species throughout rapidly warming southeast Alaska to describe long‐term changes in salmon migration timing, interannual phenological synchrony, relationships between climatic variation and migratory timing, and to test whether long‐term changes in migration timing are related to glaciation in headwater streams. Temporal changes in the median date of salmon migration timing varied widely across species. Most sockeye populations are migrating later over time (11 of 14), but pink, chum, and especially coho populations are migrating earlier than they did historically (16 of 19 combined). Temporal trends in duration and interannual variation in migration timing were highly variable across species and populations. The greatest temporal shifts in the median date of migration timing were correlated with decreases in the duration of migration timing, suggestive of a loss of phenotypic variation due to natural selection. Pairwise interannual correlations in migration timing varied widely but were generally positive, providing evidence for weak region‐wide phenological synchrony. This synchrony is likely a function of climatic variation, as interannual variation in migration timing was related to climatic phenomenon operating at large‐ (Pacific decadal oscillation), moderate‐ (sea surface temperature), and local‐scales (precipitation). Surprisingly, the presence or the absence of glaciers within a watershed was unrelated to long‐term shifts in phenology. Overall, there was extensive heterogeneity in long‐term patterns of migration timing throughout this climatically and geographically complex region, highlighting that future climatic change will likely have widely divergent impacts on salmon migration timing. Although salmon phenological diversity will complicate future predictions of migration timing, this variation likely acts as a major contributor to population and ecosystem resiliency in southeast Alaska.

Cheek pouch capacities and loading rates of heteromyid rodents - Stephen B. Vander Wall; William S. Longland; Sanjay Pyare; Joseph A. Veech (Oecologia, 1997)